1991
DOI: 10.1111/j.1464-5491.1991.tb01625.x
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐four Hour Blood Pressure and Heart Rate Profiles of Diabetic Patients with Abnormal Cardiovascular Reflexes

Abstract: Twenty-four hour ambulatory blood pressure and heart rate profiles of 24 patients with diabetes were monitored in order to assess the effect of autonomic neuropathy on 24-h haemodynamic profiles. Eighteen patients had abnormal cardiovascular reflexes. Mean arterial pressure rose at night in six of the patients with autonomic neuropathy and fell by less than or equal to 5 mmHg in seven. In the remaining five patients with autonomic neuropathy and in the six diabetic patients with normal cardiovascular reflexes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…Altered 24-h BP profiles have been found in adult diabetic patients which appear to be related to the presence of autonomic neuropathy (2,3). A decrease in nocturnal BP fall has also been observed in insulin-dependent diabetic patients with different degrees of diabetic nephropathy (4,5).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Altered 24-h BP profiles have been found in adult diabetic patients which appear to be related to the presence of autonomic neuropathy (2,3). A decrease in nocturnal BP fall has also been observed in insulin-dependent diabetic patients with different degrees of diabetic nephropathy (4,5).…”
Section: Introductionmentioning
confidence: 97%
“…The nocturnal decline in blood pressure (BP) and heart rate (HR) in healthy subjects is thought to be the result of dominating parasympathetic tone during sleep (1,2). Altered 24-h BP profiles have been found in adult diabetic patients which appear to be related to the presence of autonomic neuropathy (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That reversal of circadian BP rhythm may be related to postural hypotension and/or advanced diabetic nephropathy (16). H o w e v e r, long-term follow-up studies for NIDDM subjects in relation to circadian BP rhythms are sparse, so that the prognostic significance of the ambulatory BP pattern is not clear (17). In this study, we followed up NIDDM subjects with normal and reversed circadian BP rhythms, examined their prognoses, and determined the predictive factors of various fatal and nonfatal vascular events.…”
mentioning
confidence: 98%
“…In support of our observations, Sturrock et al (8) recently demonstrated that the combination of nondipping and subsequent renal impairment led to a higher mortality rate irrespective of diabetes type. These follow-up studies focused on the night-to-day pattern of BP variability, although the nighttime BP levels in diabetic subjects who had a poor outcome were shown to be consistently higher than the daytime BP levels (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%